2011
DOI: 10.1111/j.1468-2389.2011.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Training Success with General Mental Ability, Specific Ability Tests, and (Un)Structured Interviews: A meta-analysis with unique samples

Abstract: Several meta-analyses combine an extensive amount of research concerned with predicting training success. General mental ability is regarded as the best predictor with specific abilities or tests explaining little additional variance. However, only few studies measured all predictors within one sample. Thus, intercorrelations were often estimated based on other studies. Moreover, new methods for correcting range restriction are now available. The present meta-analyses used samples derived from a German company… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
3
35
0
1
Order By: Relevance
“…Another explanation could be that within the field of intelligence research, very elaborate models have been developed, including different intelligence facets: verbal, numerical, and figural reasoning abilities [87]. According to Brunswik's lens model [88], symmetry between predictor and criterion could increase correlations (see also [49,89]). Future studies should therefore strive to apply broad measures of Gf in Chinese contexts.…”
Section: Fluid Intelligencementioning
confidence: 99%
“…Another explanation could be that within the field of intelligence research, very elaborate models have been developed, including different intelligence facets: verbal, numerical, and figural reasoning abilities [87]. According to Brunswik's lens model [88], symmetry between predictor and criterion could increase correlations (see also [49,89]). Future studies should therefore strive to apply broad measures of Gf in Chinese contexts.…”
Section: Fluid Intelligencementioning
confidence: 99%
“…Thumin () found that a spelling test correlated significantly with performance on course content tests during training. In addition, Ziegler, Dietl, Danay, Vogel, and Bühner's () study concluded that a spelling test can be considered a good predictor of training success with operational validities of .38. The lack of conscientiousness highlighted by recruiters when they read faulty application forms is also a predictor for job performance (Barrick & Mount, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that discrimination of female applicants was more likely when hiring for a leading position (Schein et al, ) or for typical male occupations (Frauendorfer & Schmid Mast, ). Moreover, Ziegler, Dietl, Danay, Vogel, and Bühner () were able to show that no gender discrimination occurred in structured and unstructured interviews designed to select German applicants for an apprenticeship. Thus, future research should systematically vary those aspects to replicate the here reported gender fairness.…”
Section: Discussionmentioning
confidence: 99%